Pengaruh Pembelajaran Matematika Al-Qur'an dengan Model Pembelajaran Kooperatif Tipe Think Pair Share Terhadap Kemampuan Komunikasi Matematis Siswa - Syafii Muhamad Subhi; Indah Nursuprianah; Nurma Izzati (Jurnal Riset Pendidikan Matematika Jakarta, 2020)
The purpose of this research was to know: (1) students' responses to the learning of al-qur'an mathematics with cooperative learning models think pair share type; (2) mathematical communication skills of students taught by learning al-quran mathematics with cooperative learning models think pair share type; (3) the effect of learning al-quran mathematics with think pair share type cooperative learning models on students' mathematical communication skills. This research method is an experimental method with a quantitative approach and research design is the posttest-only control design. The population in this study was VII grade students of MTsNU Astanajapura Cirebon. Sampling is done by simple random sampling technique. The instruments used in the study were questionnaires and tests. The results of the study are for students' responses to learning mathematics al-quran with the cooperative learning model of the type of think pair share obtained an average percentage of 75.11% (26 students) who responded positively. For the average value of students' mathematical communication skills obtained a percentage of 77.79% so that it can be said to be good. Hypothesis test results in this study using the t test (t accent) obtained t-count > t-table (34,365> -1,706) so that the hypothesis is accepted that there is an influence on the learning of the mathematics of the qur'an with cooperative learning models think pair share type on students' mathematical communication skills.